The export potential of Uzbekistan with the use of innovative analytical tools - Sultanova L. SH, Adilov. B. B,Halmirzaev A. A.,Bekmuradov N. H. (International Journal of Advanced Science and Technology, 2020)
This article investigates major points of the export potential of Uzbekistan with the use of innovativeanalytical tools. In this article, research pinpoints feature of the methodology and theoretical pointsof the Uzbekistan with the use of innovative analytical tools. In conclusion, it makes outcomes andshortcomings of the issue export potential of Uzbekistan with the use of innovative analytical tools.